2012
DOI: 10.1021/am201757v
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Microstructure and Properties of Carbon Fiber Composites Modified with Graphene Oxide

Abstract: The performance of carbon fiber-reinforced composites is dependent to a great extent on the properties of fiber-matrix interface. To improve the interfacial properties in carbon fiber/epoxy composites, we directly introduced graphene oxide (GO) sheets dispersed in the fiber sizing onto the surface of individual carbon fibers. The applied graphite oxide, which could be exfoliated to single-layer GO sheets, was verified by atomic force microscope (AFM). The surface topography of modified carbon fibers and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
384
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 600 publications
(392 citation statements)
references
References 40 publications
6
384
2
Order By: Relevance
“…In order to exclude the possible effects of commercial sizing on the interfacial shear strength and to improve the uniformity of the porous Fig. 1 The methodology of in-situ growth of graphene-related coatings on the surface of carbon fibres carbon coating, the size on the fibre surface was removed using two different methods following the practice used by other researchers [2,11]. Using the first method, the carbon fibres were immersed into 65 wt% HNO 3 for 1.5 h. Another method allows the carbon fibres to be immersed in acetone solution for 48 h. After the removal of the size from the carbon fibre surface, the carbon fibres were fully immersed into the mixed solution mentioned above before drying the fibres in an oven at 80°C for 12 h. Then the samples were then transferred to the tube furnace with the protection of Ar/H 2 gas in a (95:5) ratio atmosphere.…”
Section: Growth Of Graphene-related Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to exclude the possible effects of commercial sizing on the interfacial shear strength and to improve the uniformity of the porous Fig. 1 The methodology of in-situ growth of graphene-related coatings on the surface of carbon fibres carbon coating, the size on the fibre surface was removed using two different methods following the practice used by other researchers [2,11]. Using the first method, the carbon fibres were immersed into 65 wt% HNO 3 for 1.5 h. Another method allows the carbon fibres to be immersed in acetone solution for 48 h. After the removal of the size from the carbon fibre surface, the carbon fibres were fully immersed into the mixed solution mentioned above before drying the fibres in an oven at 80°C for 12 h. Then the samples were then transferred to the tube furnace with the protection of Ar/H 2 gas in a (95:5) ratio atmosphere.…”
Section: Growth Of Graphene-related Coatingsmentioning
confidence: 99%
“…Properties of fibre reinforced composites are affected by the interface between fibres and matrix [2]. Fibre-matrix interfacial adhesion is extremely important since carbon fibres have chemical inertness and poor wettability with most of the polymeric matrices [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al fabricated multiscale CFRTPs by directly dispersing carbon nanotube (CNT) in the CF sizing agent. The results of mechanical tests indicated that the CFRTPs with CNT modified sizing showed 115.4% and 27.0% increases in improved interlaminar shear strength (ILSS) and impact toughness, respectively [20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to the best of our knowledge, there is a limited understanding about the fibre-matrix compatibilization and adhesion mechanisms in such high performance TP composites [7]. More precisely it is assumed that fibre-matrix interface is actually the key to improve CFRP composites [8]. Indeed, one of the challenges linked to these materials relate to the fibre-matrix interface compatibilization, adhesion promotion, ageing and improvement of damage tolerance.…”
Section: Introductionmentioning
confidence: 99%